Blind signature as a shield against backdoors in smart cards - Akhmetzyanova, L. R. (Прикладная дискретная математика)
The problem of signature forgery (including signature key recovery) in the presence of backdoors in the hardware or software of functional key carriers (smart cards) is considered. A new approach to solving the problem based on using blind signature schemes is proposed. It is shown that honest-signer blindness and honest-but-curious unforgeability of the blind signature schemes imply security against backdoors in smart cards. As a concrete example, we consider a blind version of the GOST signature scheme (the blind signature scheme proposed by Camenisch) and show that this scheme is resistant to backdoors under the single assumption that GOST is secure in the standard sense.